Human cDNA clones for an alpha subunit of Gi signal-transduction protein. - Bray, P (1987)
Two cDNA clones were obtained from a lambda gt11 cDNA human brain library that correspond to alpha i subunits of G signal-transduction proteins (where alpha i subunits refer to the alpha subunits of G proteins that inhibit adenylate cyclase). The nucleotide sequence of human brain alpha i is highly homologous to that of bovine brain alpha i [Nukada, T., Tanabe, T., Takahashi, H., Noda, M., Haga, K., Haga, T., Ichiyama, A., Kangawa, K., Hiranaga, M., Matsuo, H. & Numa, S. (1986) FEBS Lett. 197, 305-310] and the predicted amino acid sequences are identical. However, human and bovine brain alpha i cDNAs differ significantly from alpha i cDNAs from human monocytes, rat glioma, and mouse macrophages in amino acid (88% homology) and nucleotide (71-75% homology) sequences. In addition, the nucleotide sequences of the 3' untranslated regions of human and bovine brain alpha i cDNAs differ markedly from the sequences of human monocyte, rat glioma, and mouse macrophage alpha i cDNAs. These results suggest there are at least two classes of alpha i mRNA.